2017
DOI: 10.1088/2043-6254/aa5984
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of oxygen vacancies in Ce coupled TiO 2 nanocomposites by Raman and PL spectra

Abstract: CeO2–TiO2 nanocomposites with different Ce weight percentages (2, 4, 6 and 8%) were synthesized by sol-gel method. The influence of cerium inclusion on the structural, morphological, optical properties and elemental composition has been analyzed via XRD, BET surface area analysis, UV-DRS, HR-SEM, EDAX, TEM, Raman and photoluminescence spectra. The structural study showed that all the CeO2–TiO2 nanocomposites crystallized in tetragonal structure with anatase phase. Morphological study revealed that the nanocomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 59 publications
4
46
0
Order By: Relevance
“…More specifically, the anatase modes (A 1g + B 1g + 3E g ) appear at 143, 196, 396, 514, and 638 cm −1 , [32] while the rutile modes (A 1g + E g ) are observed at 446 and 608 cm −1 . [33] Although the shifting indicates an expansion of the unit cell dimensions of doped TiO 2 . While there is a broadening and shifting toward higher wavenumbers by increasing the percentage of doping.…”
Section: Ramanmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, the anatase modes (A 1g + B 1g + 3E g ) appear at 143, 196, 396, 514, and 638 cm −1 , [32] while the rutile modes (A 1g + E g ) are observed at 446 and 608 cm −1 . [33] Although the shifting indicates an expansion of the unit cell dimensions of doped TiO 2 . While there is a broadening and shifting toward higher wavenumbers by increasing the percentage of doping.…”
Section: Ramanmentioning
confidence: 99%
“…The broadening is due to the generation of oxygen vacancies by the displacement of oxide ions from their normal lattice. [33] Although the shifting indicates an expansion of the unit cell dimensions of doped TiO 2 . The shift in the E g peak increases linearly with increasing tungsten concentration and is consistent with formation of a solid solution as observed by the XRD data for the sample 5W-900.…”
Section: Ramanmentioning
confidence: 99%
“…The strong emission band at 455 nm is due to the defects on the surfaces of composites. It is reported that the green emission of the TiO 2 composites results from the surface defects formed by oxygen vacancies or the Ti interstitials on the composite surface [35].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the intensity variations suggest that the PL spectrum of TiO2 NTs with larger crystallite size is dominated by a radiative recombination of electrons via intrinsic defects states. The blue emission is visible due to the available surface energy that induces quantum confinement effect and also due to the presence of oxygen vacancies defects on the surface of TiO2 [56]. The bandgap values obtained from the PL spectrum are shown in Table 1.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…The PL peak intensities of the as-synthesized TiO 2 NTs showed a significant decrease compared to those calcined at 350, 450, and 550 • C. Furthermore, the intensity variations suggest that the PL spectrum of TiO 2 NTs with larger crystallite size is dominated by a radiative recombination of electrons via intrinsic defects states. The blue emission is visible due to the available surface energy that induces quantum confinement effect and also due to the presence of oxygen vacancies defects on the surface of TiO 2 [56].…”
Section: Optical Propertiesmentioning
confidence: 99%